A van der Waals Ferroelectric Tunnel Junction for Ultrahigh‐Temperature Operation Memory. Issue 4 (25th February 2022) - Tang, Wenhui; Zhang, Xiankun; Yu, Huihui; Gao, Li; Zhang, Qinghua; Wei, Xiaofu; Hong, Mengyu; Gu, Lin; Liao, Qingliang; Kang, Zhuo; Zhang, Zheng; Zhang, Yue
Abstract: Facing the constant scaling down and thus increasingly severe self‐heating effect, developing ultrathin and heat‐insensitive ferroelectric devices is essential for future electronics. However, conventional ultrathin ferroelectrics and most 2D ferroelectric materials (2DFMs) are not suitable for high‐temperature operation due to their low Curie temperature. Here, by using few‐layer α‐In2 Se3, a special 2DFM with high Curie temperature, van der Waals (vdW) ferroelectric tunnel junction (FTJ) memories that deliver outstanding and reliable performance at both room and high temperatures are constructed. The vdW FTJs offer a large on/off ratio of 10 4 at room temperature and still reveal excellent on/off ratio at an ultrahigh temperature of 470 K, which will fail down other 2DFMs. Moreover, long retention and reliable cyclic endurance at high temperature are achieved, showing robust thermal stability of the vdW FTJ memory. The observations of this work demonstrate an exciting promise of α‐In2 Se3 for reliable service in high temperature either from self‐heating or harsh environments. Abstract : Developing heat‐insensitive memory is crucial for future electronics which are facing the severe self‐heating effect. By using 2D ferroelectric α‐In2 Se3 with a high Curie temperature, the authors report a van der Waals ferroelectric tunnel junction memory that delivers outstanding and reliable performance at high temperatures, which demonstrates an exciting promise of α‐In2 Se3 for antagonizing unavoidable temperature rising due to self‐heating.